Enhancing Institutional Performance of Tutoring Centers in Kuala Lumpur: The Role of Document-Based Budget Management - Winarno, Agung; Nur Aini, Desti; Retnaningsih, Prihatini; Rahman, Amalia Arifah (Journal of Applied Business, Taxation and Economics Research, 2023)
Effective budget management is pivotal for any institution, acting as a linchpin for informed decision-making. Central to this study is the exploration of how document-based budget management applications can substantially augment the quality of institutional performance. Specifically, this research focuses on the Jalan Kebun Tutoring Center, which serves the children of Indonesian expatriates employed in Selangor, Malaysia. The chosen methodological approach for this study is applied research via a case study format. Data interpretation relies on comparative descriptive analysis. The research progression encompasses several stages: needs identification, application development, testing, results revision, and, finally, implementation. The findings underscore the escalating demand for a dedicated application to streamline financial accounting processes. This urgency is heightened by the expansive growth of institutions and the increasing demand from various stakeholders for transparent financial reporting. Notably, the pilot testing of the application affirmed its capacity to bolster speed, precision, and efficiency in disseminating crucial financial information to relevant parties. An essential recommendation stemming from this study is the potential integration of this financial application with academic processes. Such an integration could present a holistic view, offering comprehensive information that bridges both academic and financial spheres, ensuring a unified institutional management approach.